Timeshare industry leadership and human resource implications of employee and guest satisfaction - Maier, Thomas A., (SAGE Business Cases., 2013)
Kalalau Timeshare/Vacation Ownership Inc. was founded in 2001 and currently owns, operates and manages 30 resorts across 8 states in the US. At the annual strategic conference the CEO of Kalalau Timeshare/Vacation Ownership Inc. wants a closer examination of a few key factors associated with company performance; employee satisfaction, customer satisfaction and facilities maintenance. Students are asked to examine the data on employment and staff satisfaction and make strategic recommendations for how Kalalau Inc. should proceed.